Affecting Biotik and Abiotic Components Cultivation of Oyster Mushroom (Pleurotus ostreatus) in Kualanamu, North Sumatera - Safitri, Riri; Munthe, Novita Br Ginting (Universitas Labuhanbatu, 2022)
Oyster mushroom (Pleoratus ostreatus) is one of the mushroom species cultivated by residents of Pasar VI Kualanamu Village, Beringin District, Deli Serdang Regency, North Sumatra Province. Residents gain knowledge of oyster mushroom cultivation through the training provided. Therefore, researchers are interested in conducting research in Pasar VI Kualanamu Village. The purpose of this study is to determine the biotic and abiotic components that can affect the growth of oyster mushrooms and what efforts need to be made so that they can cultivate oyster mushrooms and increase their production. The research carried out is a type of field research that is descriptive qualitative, namely research that describes existing phenomena by finding patterns of interactive relationships, discovering new theories, describing complex realities and gaining understanding of meaning. In this study, the researcher was involved as a participant observer to further explore the research process carried out. From the results of the study it can be concluded that the biotic and abiotic components that can affect the growth of oyster mushrooms (Pleurotus ostreatus) are kumbung building materials (mushroom houses), pests in kumbung (mushroom houses), sunlight, water, sterilization of materials (wood powder & bran), soil temperature and humidity, planting and harvesting media